In vitro schistosomicidal activity of the lignan (−)-6,6'-dinitrohinokinin (DNHK) loaded into poly(lactic-co-glycolic acid) nanoparticles against Schistosoma mansoni - Thaís C. Lima; Rodrigo Lucarini; Priscilla P. Luz; Emerson H. de Faria; Liziane Marçal; Lizandra G. Magalhães; Fernanda R. Badoco; Viviane R. Esperandim; Eduardo F. Molina; Rosangela S. Laurentz; Regiane G. Lima; Wilson R. Cunha; et al. (Taylor & Francis Group, 2017)
Context: (−)-6,6'-Dinitrohinokinin (DNHK) display remarkable antiparasitic activity and was, therefore, incorporated into a nanoparticle formulation. Objective: Incorporation of DNHK in poly lactic-co-glycolic acid (PLGA) nanoparticles aiming to improve its biological activities. Materials and methods: Synthesis, characterization and incorporation of DNHK into glycolic acid (PLGA) nanoparticles by nanoprecipitation method. The nanoparticles were characterized by ultraviolet-visible spectroscopy, X-ray diffraction, field emission electron microscopic scanning mansoni (FESEM), and dynamic light scattering (DLS). For the in vitro test with Schistosoma mansoni, the DNHK-loaded PLGA was diluted into the medium, and added at concentrations 10-200 µM to the culture medium containing one adult worm pair. The parasites were kept for 120 h and monitored every 24 h to evaluate their general condition, including: pairing, alterations in motor activity and mortality. Results: The loaded PLGA nanoparticles gave an encapsulation efficiency of 42.2% and showed spherical characteristics in monodisperse polymeric matrix. The adult worm pairs were separated after 120 h of incubation for concentrations higher than 50 µM of DNHK-loaded PLGA. The groups incubated with 150 and 200 µM of DNHK-loaded PLGA for 24 and 120 h killed 100% of adult worms, afforded LC50 values of 137.0 ± 2.12 µM and 79.01 ± 1.90 µM, respectively, which was similar to the effect displayed by 10 µM of praziquantel. Discussion and conclusions: The incorporation of DNHK-loaded showed schistosomicidal activity and allowed its sustained release. The loaded PLGA system can be administered intravenously, as well as it may be internalized by endocytosis by the target organisms.